Gaya Komunikasi Kepemimpinan Kaum Tertindas Dalam Film War For The Planet Of The Apes - Shohibul Padli; Fitri Meliya Sari; Fairus Fairus (Journal of Innovative and Creativity, 2026)
This study aims to analyze the leadership communication style displayed by the leader of the oppressed in the film War For The Planet Of The Apes. A qualitative approach with semiotic analysis methods is used to identify and interpret visual, verbal, and nonverbal signs that represent leadership communication practices. The results of this study found that the character Caesar uses a transformative, empathetic, and symbolic communication style in his efforts to unite and lead the ape community in facing human oppression. Nonverbal communication, such as facial expressions, body movements, and eye contact, are central elements in conveying the values of solidarity, steadfastness, and hope. Thus, the study concludes that the leadership communication style displayed in this film not only functions as a coordination tool, but also as a means of forming a collective identity and resistance against the hegemony of the ruler.